Serum galectin-3 in chronic kidney disease: association with disease stage and value after kidney transplantation - Hao, Dinh Thi Minh; Tam, Vo (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Serum creatinine is a traditional marker in chronic kidney disease, which is valuable in monitoring renal function and prognosis after kidney transplantation. Recently, several novel biomarkers have been introduced to diagnose and predict chronic kidney disease as well as monitor kidney transplant function. Galectin-3 is one such marker. Increased galectin-3 concentration has been reported to be associated with renal fibrosis. High serum galectin-3 concentration is also associated with the risk of rapid renal function decline, new chronic kidney disease and progressive renal failure, as well as predicting events and mortality in patients with renal impairment. Methods: A cross-sectional analytical study was conducted at Hue Central Hospital from October 2024 to October 2025. Patients with CKD stages 3-5, patients receiving maintenance hemodialysis, and stable kidney transplant recipients at 3 months post-transplantation were enrolled. Serum galectin-3 concentrations were measured using chemiluminescent microparticle immunoassay on the Abbott Alinity platform at Biochemistry Department - Hue Central Hospital. Results: A total of 172 pre-transplant CKD patients and 32 post-transplant recipients were included. Mean serum galectin-3 level in the CKD group was 53.97 ± 25.68 ng/mL and increased progressively with disease severity: stage 3 (28.87 ± 8.02), stage 4 (44.77 ± 17.07), stage 5 non-dialysis (56.69 ± 20.66), and maintenance hemodialysis (72.75 ± 24.86 ng/mL) (p < 0.001). Galectin-3 level decreased markedly after transplantation (15.25 ± 5.97 ng/mL). Serum galectin-3 was positively correlated with creatinine (r = 0.605, p < 0.001) and negatively correlated with estimated glomerular filtration rate (eGFR) (r = -0.627, p < 0.001). Conclusion: Serum galectin-3 levels rise with CKD progression and decline significantly after kidney transplantation. Galectin-3 may serve as a useful biomarker for disease severity assessment and post-transplant monitoring.